Study on the Influence of Live Broadcast with Goods on Enterprise Operation and Product Price : Take Anta for example - Zhu, Dawei (International Journal of Global Economics and Management, 2024)
At present, China’s economic growth situation from the high speed stage to the high quality stage, emerging industries emerge in an endless stream. With the rapid development of the Internet, live streaming, as an emerging e-commerce consumption mode, has risen rapidly in recent years and has attracted wide attention from all walks of life. The paper first uses the PEST model to analyze the overall environment of the live delivery industry. Secondly, the paper selects the practice of Anta Group implementing live goods as a case, and deeply discusses how to effectively carry out live goods activities, so as to positively promote the improvement of the enterprise’s operation efficiency. Finally, it is concluded that the potential of live streaming is huge and will have a positive impact on the operation and price, but there are also some potential risks.